Financial Behaviors, Couple‐Level Conflict, and Adolescent Relationship Abuse: Longitudinal Results From a Nationally Representative Sample. (19th December 2018) - Copp, Jennifer E.; Taylor, Bruce G.; Mumford, Elizabeth A.
Abstract : Financial disagreements have been identified as a severe source of discord in adult relationships, yet limited work has considered whether financial considerations contribute to conflict among younger samples. Drawing on longitudinal data from a nationally representative sample of adolescents, the current investigation examined the extent to which money lending practices, feelings of financial resentment, and exposure to economic control contribute to couple‐level interactions, and in turn, to conflict that escalates to the point of violence. Findings provide evidence of an association between adolescent financial behaviors and concurrent conflict due to economic considerations. Moreover, conflict due to economic considerations was an important predictor of future adolescent relationship abuse perpetration. We discuss the implications of our findings for intervention/prevention efforts.